Meta-analysis and systematic review: burosumab as a promising treatment for children with X-linked hypophosphatemia - Wang, Kangning; Zhang, Runze; Chen, Ziyi; Bai, Yi; He, Qing (Frontiers in Endocrinology, 2024)
The aim of this study was to evaluate the effectiveness of burosumab therapy in children with X-Linked Hypophosphatemia (XLH).We systematically reviewed literature from PubMed, Web of Science, The Cochrane Library, and Embase up until January 2024, using EndNote Web for study organization. The Newcastle-Ottawa scale guided quality assessment, while Revman software was used for data analysis and visualization. Study selection, 2 quality evaluation, and data aggregation were independently performed by three researchers.The meta-analysis encompassed ten studies, including eight cohort studies that examined burosumab's impact pre-and post-administration, and two randomized controlled trials comparing burosumab to standard therapy. The evidence from this review suggests burosumab's superiority in managing XLH in pediatric populations, particularly in improving key biochemical markers including 1,25-dihydroxyvitamin D (1,25-(OH)2D), phosphorus, and alkaline phosphatase (ALP), alongside improvements in the renal tubular maximum reabsorption rate of phosphate to glomerular filtration rate (TmP/GFR), and significant skeletal improvements as indicated by the rickets severity score (RSS) and the 6-minute walk test (6MWT).However, the long-term safety and effects, including height and quality of life (QOL) data, remains to be elucidated.: Burosumab has shown significant therapeutic effectiveness in treating children with XLH, highlighting its potential as a key treatment option. or obviously representative series of cases ✯, (b) potential for selection biases or not stated. g (a) community controls ✯,(b) hospital controls, (c) no description. h (a) no history of disease (endpoint) ✯, (b) no description of source. i (a) the exposures of interest (burosumab and active control) were adjusted for one confounder ( sex or age) ✯, (b) the exposures of interest (burosumab and active controll) were adjusted for two or more confounders ( sex or age and treatment compliance or severity of illness) ✯✯, c) no description. j (a) secure record (e.g., surgical records) ✯, (b)structured interview where blind to case/control status ✯, (c) interview not blinded to case/control status, (d) written self-report or medical record only, (e) no description. k (a) yes ✯, (b) no. l (a) same rate for both groups ✯, (b) non-respondents described, (c) rate different and no designation.